PENGEMBANGAN PARIWISATA MELALUI PEMBERDAYAAN MASYARAKAT DILIHAT DARI PERSPEKTIF IMPLEMENTASI KEBIJAKAN - Ikke Febriandhika; Teguh Kurniawan (Universitas Merdeka Malang, 2020)
Tourism has an important contribution to development, so to realize sustainable tourism requires effective policy and planning. Then, one of the pillars in tourism development strategies is through community empowerment. However, in the tourism development policy implementation through community empowerment doesn’t work as planned. The purpose of this study is to offer a review of the tourism development policy through community empowerment and what are influencing factors of the tourism development policy implementation through community empowerment. This study used qualitative research methods through literature studies. These study findings show that tourism development policy through community empowerment have to prioritize the needs of the local community itself, in addition the aspects of tourists and tourism service providers. Tourism development policy comes from the community, by the community, and for the community. Through community empowerment can increase participation and active involvement of local community in order to develop local tourism. Factors affecting tourism development policy through community empowerment consist of internal and external factor. Internal factors related to social, cultural, environmental, and local resources. While external factors related to political support and interest groups within the tourism policy itself.